2015
DOI: 10.1007/s11881-015-0106-y
|View full text |Cite
|
Sign up to set email alerts
|

Risk and protective factors in gifted children with dyslexia

Abstract: This study investigated risk and protective factors associated with dyslexia and literacy development, both at the group and individual level, to gain more insight in underlying cognitive profiles and possibilities for compensation in high-IQ children. A sample of 73 Dutch primary school children included a dyslexic group, a gifted-dyslexic group, and a borderline-dyslexic group (i.e., gifted children with relative literacy problems). Children were assessed on literacy, phonology, language, and working memory.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
29
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 49 publications
5
29
0
5
Order By: Relevance
“…Although some researchers have suggested that students with compensated dyslexia succeed in school, in part, because of strong verbal language abilities (Snowling and Melby‐Lervåg , van Viersen et al . ), a clear conclusion awaits further research.…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…Although some researchers have suggested that students with compensated dyslexia succeed in school, in part, because of strong verbal language abilities (Snowling and Melby‐Lervåg , van Viersen et al . ), a clear conclusion awaits further research.…”
Section: Introductionmentioning
confidence: 91%
“…, van Viersen et al . ). In recent years, dyslexia has been reconceptualized as the combined sum of risk factors and protective factors (e.g., Cavalli et al .…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations